Determinants of Participation of Smallholder Coffee Farmers in Warehouse Receipt System in Mbinga District, Tanzania - Mapunda, Matei; Mhando, David; Waized, Betty (Tanzania Journal for Population studies and Development, 2019)
The Warehouse Receipt System (WRS) holds considerable opportunities necessary for improving incomes and livelihoods of smallholder farmers. However, there has been little progress regarding participation of smallholder farmers in the system. This paper examines factors that influence smallholder coffee farmers’ participation in the WRS. The specific objective was to identify factors influencing participation. A random household survey of 390 farmers was conducted in Mbinga District, Tanzania. Data were analysed using binary logistic regression. The results show that a respondent’s age, market information, sex, and distance from coffee farms to Agricultural Marketing and Cooperative Societies (AMCOS) or farmers’ group (FG) centres influenced coffee farmers’ decisions to participate in the WRS. Young, male farmers with access to coffee market information are more likely to use the WRS. Dissemination of the market information and the location of AMCOS or FG centres closer to coffee farmers could be a key to increasing farmers’ participation in the WRS.